Parental Assistance In Learning From Home Activities To Self-Efficacy In Children Aged 4-6 Years - Delina Kasih; Fitria Budi Utami (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
This study aimed at analyzing the effect of parental assistance in learning activities from home on the self-efficacy in children aged 4-6 years in RW 03 Rawa Bunga, Jatinegara, East Jakarta. This research used the survey method and Pearson Bivariate Correlation analysis. Samples were taken 55% of the total population, namely 30 parents. The sampling technique used in this research was purposive sampling. The data collection technique used in this research was a questionnaire technique (questionnaire) for the two variables. This study resulted in a regression equation Y= 49.011 + 0.511X with the results of the correlation coefficient test yielding 0.429; and the coefficient of determination 18.4% interpreted the effect of parental assistance in learning activities from home on the self-efficacy in children aged 4-6 had a significant positive effect, the influence of parental assistance had a sufficient correlation on children's self-efficacy and parental assistance has an effect of 18.4% of the self-efficacy in children aged 4-6 years in RW 03 Rawabunga, Jatinegara, East Jakarta.